Toxicity of Azadirachta indica and Piper sarmentosum extract mixture formulations against Nilaparvata lugens Hemiptera: Delphacidae in paddy field - Mawi, Masdah; Mat Saad, Muhamad Hanzalah; Mokhtar, Anis Syahirah; Asib, Norhayu (Universiti Kebangsaan Malaysia, 2022)
Infestation of Nilaparvata lugens on rice in Malaysia is not as heavy compared to other Asian countries, but still lower the rice yield production. Nilaparvata lugens is developing resistance against chemical pesticide, therefore an alternative approach such as the application of botanical pesticide is potential to control the N. lugens. The aims of this research were to determine the synergistic activity in combination of Azadirachta indica and Piper sarmentosum emulsion formulations extract against Nilaparvata lugens. Three formulations were developed were coded as F1, F2, and F3. The F1 was selected as the best formulation because it in range of good zeta potential value (-48.3 mV) and viscosity value (100.1 mPa/s), the lowest particle size (202.5 nm), remained homogenous for centrifugation and stability test, polydispersity index (PDI) value indicated it is in ideal monodisperse phase (0.359), low surface tension (31.3 mN/m) and low pH (3.65). The lethal concentration, LC50 and sub lethal, LC10 and LC25 were determined from nymph mortality bioassay test on third instar N. lugens nymphs. Mortality rate of F1 and F2 were 0.011 mg/l and F3 was 0.031 mg/l. The value of lethal and sublethal concentration were used in a test against female N. lugens to determine the effect of formulations on fecundity of N. lugens. There were significant differences between formulations on the number of eggs produced after treatments. The lowest egg produced from F1 with 128.11 number of eggs. It can be concluded that all formulations showed promising result in controlling N. lugens.